Differences in Brain Activity for Temporal Lobe Epilepsy Patients and Healthy Subjects: Findings from Resting-state fMRI - Jan Mohamed, Shuhada; Mohd Amin Rebuan, Husbani; Yusoff, Ahmad Nazlim; Abd Hamid, Aini Ismafairus (IIUM Medical Journal Malaysia, 2022)
INTRODUCTION: Temporal lobe epilepsy (TLE) is a chronic disorder of the nervous system with focal seizures that may spread to other brain regions. Present knowledge regarding the spread of seizure is scarce. This study investigated activity in brain regions outside temporal lobe of TLE patient (TLEP) that may be affected by the spread. The findings were compared with healthy subject (HS). MATERIALS AND METHODS: Resting-state functional MRI (rsfMRI) were performed on 14 TLEPs and 14 HSs. Spatial activation, laterality index (LI) and functional connectivity (FC) involving several brain regions were analysed. RESULT: Bilateral precuneus (PRE) and supramarginal gyrus (SMG) which were activated (puncorr.<0.001) outside the temporal lobe were chosen for analysis. In the left and right hemispheres, two-way analysis of variance (ANOVA) showed a significant difference between PRE and SMG activation (p<0.001) but not between TLEP and HS (p>0.001). SMG was found to be moderately right-lateralised in both TLEP and HS with LI = -0.309 and -0.125, respectively. For PRE, HS showed moderate left lateralisation (LI = 0.121), while TLEP showed weak right lateralisation (LI= -0.002). FC results revealed that the activity in PRE and SMG changed over time for HS and TLEP but only in the left hemisphere. CONCLUSION: Although resting-state activations in the two selected brain areas outside the temporal lobe in both hemispheres were incomparable between TLEP and HS, evidences from LI and FC analyses suggested anomalies especially in the left hemisphere that could be due to the spread of seizure.